A merenda escolar e seu potencial em face da segurança alimentar em Guaribas-PI - Negreiros, Fauston (2009)
It is a study about The National Program for Free School Meal (NPFSM) as an instrument with the potential for social development and promotion of the quality of life in the midst of hunger present in the town of Guaribas-PI. It is an effort to map out the universe of family agricultural production at the town, identifying the foods that can be integrated into the menu of school meal; and to present the eating practices of the population of the town situating its social-historical and cultural construction. The method utilized was qualitative, Oral History, with the research approach defined as explorative-explanative, in which it was necessary groups of participants contemplated by the residents of Guaribas, the parents of the students, technicians responsible for school meal and through the analysis of the potentialities of the geographical region. These are the studies around the curriculum theory, the social-anthropological concepts of food and nourishment, agricultural production and the situation of hunger, cultural aspects of the dry regions of Piauí and the eating practices in school spaces, which represent the theoretical base of the investigation. The analysis of the data was done according to the orientations of the Depth Hermeneutics, through which it was given the emphasis on the process of the interpretation, making possible the comprehension of the symbolic forms as field-object and also field-subject. Through this study, we can establish that the ways of the utilization of the NPFSM- educational policy- can constitute the potential element of the stimulus to the local and family agriculture and for the overcoming of hunger, enabling to guarantee food security. However, this does not happen, in its plenitude, in the operationalization of the Program for the town of Guaribas-PI.